Well-posedness of the Dirichlet and Poincare problems for a multidimensional Gellerstedt equation in a cylindric domain - Aldashev, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We prove the unique solvability of the Dirichlet and Poincare problems for a multidimensional Gellerstedt equation in a ´cylindric domain. We also obtain a criterion for the unique solvability of these problems.